2007
DOI: 10.1897/06-355.1
|View full text |Cite
|
Sign up to set email alerts
|

Cholinesterase activity as a biomarker of pesticide exposure inAllolobophora chloroticaearthworms living in apple orchards under different management strategies

Abstract: The present study used cholinesterase (ChE) activity in earthworms as a biomarker of pesticide exposure at 17 apple orchards using different pest protection strategies (organic, integrated pest management [IPM], conventional, and abandoned) located within a 300-km(2) subregion near Avignon in southeastern France). The most common earthworm species in the 17 orchards was Allolobophora chlorotica. We examined inherent variability in ChE activity that might be attributable to soil characteristics and found that d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 36 publications
0
15
1
Order By: Relevance
“…In contrast, Denoyelle et al [30] showed a significant inhibition of cholinesterase activity under pesticide exposure working in orchard field experiments, with variations due to the different pest protection strategies. These differences in ChE inhibition could be explained by different factors, including the nature of the sprayed pesticides, the quantities applied, the period of pesticide spraying [41], the earthworm species [71] and the soil properties [7].…”
Section: Impact Of Vineyard Soil Management On Pesticide Ecotoxicity mentioning
confidence: 87%
See 3 more Smart Citations
“…In contrast, Denoyelle et al [30] showed a significant inhibition of cholinesterase activity under pesticide exposure working in orchard field experiments, with variations due to the different pest protection strategies. These differences in ChE inhibition could be explained by different factors, including the nature of the sprayed pesticides, the quantities applied, the period of pesticide spraying [41], the earthworm species [71] and the soil properties [7].…”
Section: Impact Of Vineyard Soil Management On Pesticide Ecotoxicity mentioning
confidence: 87%
“…Using the same pesticide mixture (chlorpyrifos-ethyl and lcyhalothrin as insecticides and folpet, metalaxyl-M, fosetyl-Al and myclobutanil as fungicides) in controlled experiments, Schreck et al [24] concluded that there was an inhibition of ChE activity in exposed earthworms. The limitations of the extrapolation of ecotoxicity results from laboratory conditions to field experiments was previously highlighted by Denoyelle et al [30] and Laszczyca et al [67]. However, numerous studies in microcosms are still performed to assess the impact of pollutants on earthworms [19e24] and only few investigations are carried out under field conditions [32].…”
Section: Impact Of Vineyard Soil Management On Pesticide Ecotoxicity mentioning
confidence: 99%
See 2 more Smart Citations
“…The biochemical biomarkers are being utilized these days for the analysis of pollutant toxicity, metabolization and detoxification in earthworm [13] [14] which later can be used for the detection and assessment of contaminant that influence the environmental modifications [15].…”
Section: Introductionmentioning
confidence: 99%